Symmetry‐Induced Singlet‐Triplet Inversions in Non‐Alternant Hydrocarbons. Issue 15 (3rd March 2023) - Terence Blaskovits, J.; Garner, Marc H.; Corminboeuf, Clémence
Abstract: Molecules with inversion of the singlet and triplet excited‐state energies are highly promising for the development of organic light‐emitting diodes (OLEDs). To date, azaphenalenes are the only class of molecules where these inversions have been identified. Here, we screen a curated database of organic crystal structures to identify existing compounds for violations of Hund's rule in the lowest excited states. We identify two further classes with this behavior. The first, a class of zwitterions, has limited relevance to molecular emitters as the singlet‐triplet inversions occur in the third excited singlet state. The second class consists of two D 2 h ‐symmetry non‐alternant hydrocarbons, a fused azulene dimer and a bicalicene, whose lowest excited singlet states violate Hund's rule. Due to the connectivity of the polycyclic structure, they achieve this symmetry through aromatic stabilization. These hydrocarbons show promise as the next generation of building blocks for OLED emitters. Abstract : A new class of molecules displaying an inversion of the lowest singlet and triplet excited states has been identified through computational screening of synthesized structures. This observed behavior is attributed to a high‐symmetry pentalene core motif, which is stabilized via aromaticity.